The Impact of Gender Quotas on The Management of Local Government Units - Magdalena Roman (Communications of International Proceedings, 2023)
Human capital plays a crucial role in the management of local government units.  The article presents the impact of human capital management - gender quotas on the financing of local government units - municipal, county, provincial councils. The topic of gender quotas in local government is not often discussed. Financing local government units in a changing economic landscape becomes increasingly challenging. Decisions of local government officials heading local government units are influenced by many factors including gender structure and changing environment. The structure of councilors in all three local government units by male and female is presented. The structure of councilors in the above-mentioned units is presented on the basis of data from the year 2021. The share of men and women in each local government unit and thus the distribution of gender parity is determined. Based on the collected data, it can be concluded that the largest difference between the number of provincial councilors is found in the Kujawsko-Pomorskie and Lubelskie provinces, and the smallest in the Łódzkie province. As far as county councilors are concerned, the largest gender parity disproportion with a male advantage is found in the districts of the Mazowieckie, Wielkopolskie and Malopolskie provinces. In municipal councils, as in provincial and county councils, men prevail. The smallest gender differences are found in four provinces: lubuski, opolski, świętokrzyski, warmińsko-mazurski. In general, it should be said that gender parity has not been maintained in all of these cases. Local government in Poland has a long way to go before gender parity is equalized in accordance with the European Charter for Equality between Women and Men.
Keywords: quotas; management; human capital; local government units